Effects of seed rate and inter row spacing on yield and yield components of food barley in Semen Ari Woreda, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
A field experiment was carried out for two successive cropping seasons in 2017 and 2018 at Shama Bulket, Semen Ari Woreda, South Omo Zone, Southern Ethiopia, to determine optimum seed rate and inter-row spacing for food barley production. The experiment involved a factorial combination of three seed rates (80, 100 and 120 kg ha-1) and three inter-row spacing (20, 30 and 40 cm). The experiment was conducted using a randomized complete block design with three replications. The results indicated the treatments had significant effect in all parameters except plant height and spike length. Based on the result of this study, use of 30 cm inter-row spacing and 120 kg ha-1 seed rate is superior in grain yield (4481 kg ha-1) and total biomass (14.6 t ha-1). Therefore, use of 30 cm inter row spacing with seeding rate of 120 kg ha-1 can be recommended for food barley production at Shama Bulket kebele and its vicinity.Int. J. Agril. Res. Innov. Tech. 12(1): 34-38, June 2022